Reflections on the Pandemic, Online Learning, and the Outcomes of Faith-based Education - Gayoba, Francis D. (8ISC Abstract Proceedings, 2022)
The shift to fully-online learning due to the COVID-19 pandemic has posed challenges to delivering the outcomes of faith-based tertiary-level boarding schools. The mission of faith-based schools is to transform students into the kinds of persons their religious traditions envision their members should be. This paper addresses the issue of whether faith-based schools can fulfill such as a mission in the context of the long-term use of online learning. The reflection first examines whether online-learning outcomes align with faith-based schools' educational theory and curriculum goals. Secondly, the paper considers insights from neuroscience and education on the impact of online learning on the wholistic development of students. The paper concludes that, first, the long-term use of online learning does not fully provide a community experience needed to develop faith. Secondly, the effects of prolonged use of online learning result in changes in the student’s brains that undermine faith maturity. Some suggestions are provided on how to temporarily compensate such limitations and effects so that faith-based schools can still partially fulfill their mission in the context of online learning due to the pandemic. Keywords : online-learning, faith-based, education